Investigation on Airborne Fungi in Sheep Houses - Abdalla, Wisal, G. (Journal of Veterinary Medicine and Animal Production, 2021)
Besides the well-known allergens, several other risk factors may exist for health in animals’ house. The exposure to these factors may be significant in animal units especially those with poor ventilation. This study was carried out to investigate the presence of airborne fungi in sheep fences. Eight fungal species were identified from air samples after diagnostic examination. Penicillium, Aspergillus, Alternaria and Fusarium were the predominant fungal genera.